ANALISIS KALIBRASI ELECTROSURGICAL UNIT DI RSU Dr H.KUMPULAN PANE TEBING TINGGI - feriyanta - purba (Saintia Fisika, 2013)
Testing and calibration of electrosurgical ARC 350 has been performed Using Electrosurgical analyzer, safety analyzer 601 and held at Balai Pengamanan Fasilitas Kesehatan (BPFK) Medan.This study aimed to obtain information about the method of testing and calibration of the Electrosurgical and to know the result of calibration data are based on the test procedures and calibration of the Electrosurgical from the Balai Pengamanan Fasilitas Kesehatan Republik Indonesia , with the proviso that the Electrosurgical output energy is in threshold of (± 10 % for energy cutting and energy coagulation) of the setting at the timeof testing .From the result of research conducted has been known that the Electrosurgical merk Bowa ARC 350 which has been tested is feasible to use.